Original paperApplication of immunohistochemistry for detection of metastases in sentinel lymph nodes of non-advanced breast cancer patients - Nowikiewicz, Tomasz; Śrutek, Ewa; Zegarski, Wojciech (Polish Journal of Pathology, 2015)
Any diagnostic method for detection of occult metastases in sentinel lymph node (SLN) could change postoperative therapeutic management. In this study, we attempted to evaluate the usefulness of immunohistochemical (IHC) studies for histopathological SLN examination and their impact on the diagnosis of metastatic lesions. Analyzed data concerned 1358 breast cancer patients referred for sentinel lymph node biopsy (SLNB) between 2004 and 2012 with particular emphasis on broadening the scope of postoperative SLN histopathological assessment to include IHC. Sentinel lymph node involvement was diagnosed in 22.2% of patients. Use of the IHC method facilitated detection of 21.4% of all diagnosed SLN lesions (9.9% of macrometastases, 60.0% of micrometastases, 100% of isolated tumor cells). 61.6% sensitivity and 100% specificity were obtained in the group of patients who underwent intraoperative SLN histopathological examination. Use of immunohistochemistry for diagnostics of sentinel lymph node metastases in patients with breast cancer enables detection of a greater proportion of metastases, thus modifying both surgical (SLN macrometastases) and adjuvant treatment. As compared to pN0 patients and those with a metastasis found in HE staining, in patients with a metastasis in the sentinel lymph node diagnosed in IHC studies, no statistically significant differences were found concerning the long-term results of the implemented treatment.